Corrosion inhibition of locally de-passivated surfaces by DFT study of 2-mercaptobenzothiazole on copper - Fatah Chiter (Nature Portfolio, 2021)
Abstract Investigating the interaction of organic inhibitors with metal and alloy surfaces is crucial for an atomic-scale understanding of their protection efficiency, particularly on the initiation of localized corrosion by pitting. Quantum chemical DFT calculations were performed to optimize the constructed model of a depassivated copper surface and to study the adsorption of 2-mercaptobenzothiazole (MBT), on different zones exposed by local depassivation. Reactive sites exist at the metal surface, at the oxide surface, as well as on the oxide edges and oxide walls. The surface-reactive sites are the unsaturated and saturated copper atoms and singly and doubly unsaturated oxygen atoms of the oxide, and the copper atoms of the metal. The sulfur (Sexo and Sendo) and nitrogen (N or NH) atoms are the reactive sites in the molecules. MBT can covalently bond to the oxide surface as well as to the oxide edges, oxide walls, and metal surface exposed by depassivation. For the thione species, local adsorption strength decreases as oxide edges > oxide surface > metal surface > oxide walls, suggesting that MBT heals the low coordinated sites. For the thiolate species, adsorption strength is similar on the different area, except the oxide walls. The results show the ability of the inhibitor to interact on different zones of a locally depassivated surface and to form a strongly adsorbed organic film, which can block the initiation of localized corrosion by enhancing the interfacial barrier properties, including in the local surface areas incompletely passivated or locally damaged by depassivation.